Morphological Asymmetries Profile and the Difference between Low- and High-Performing Road Cyclists Using 3D Scanning - Samo Rauter (MDPI AG, 2021)
The aims of this study are: (1) to identify morphological asymmetries in road cycling by using a novel 3D scanning method and electrical bioimpedance, (2) to investigate possible asymmetries in road cyclists of low (LPG) and high (HPG) performance group, (3) to compare the number of morphological asymmetries between HPG and LPG of cyclists, and (4) to explore correlations between asymmetry scores and competition performance. Body composition and 3D anthropometric measurements were conducted on 48 top-level male road cyclists (178.98 ± 5.39 cm; 68.37 ± 5.31 kg) divided into high (n = 22) and low (n = 26) performance groups. Competition performance (CP) is represented through racing points gathered at the end of the competition season. The latter was used to divide road cyclists into low- and high-performing groups. One-way ANOVA was used to determine differences between groups, while paired-samples T-test and Absolute Asymmetry index (AA) were calculated (p ≤ 0.05) for paired variables inside the groups, and the Spearman correlation coefficient was used to explore correlations between AA and CP. Results showed statistically significant differences between the left and right side of different body segments (16 paired variables) among low-performing road cyclists in five paired variables of the upper body: elbow girth (4.35, p = 0.000), forearm girth (6.31, p = 0.000), arm surface area (2.54, p = 0.018), and arm volume (2.71, p = 0.012); and six paired variables of the lower body: leg lean mass (5.85, p = 0.000), leg length (3.04, p = 0.005), knee girth (4.93, p = 0.000), calf girth (5.25, p = 0.000), leg surface area (4.03, p = 0.000), and leg volume (5.3, p = 0.000). Altogether, the high-performing group of road cyclists statistically differed only in 2 out of 16 paired variables of the upper body: elbow girth (4.93, p = 0.000) and in forearm girth (5.12, p = 0.000). Low- and high-performing groups were statistically significantly different in the asymmetry of leg lean mass F(1,46) = 6.25, p = 0.016 and asymmetry of the calf girth F(1,46) = 7.44, p = 0.009. AA of calf girth on the total sample (n = 48) showed a significant correlation with CP (r = −0.461; p = 0.001). In conclusion, the study’s main finding was that high-performance road cyclists are more symmetrical than the low-performance group, for which it is significant to have a higher amount of morphological asymmetries.